Influence of Palm Oil Fuel Ash and W/B Ratios on Compressive Strength, Water Permeability, and Chloride Resistance of Concrete - Wachilakorn Sanawung; Tieng Cheewaket; Weerachart Tangchirapat; Chai Jaturapitakkul (Advances in Materials Science and Engineering)
This research studies the effects of W/B ratios and palm oil fuel ash (POFA) on compressive strength, water permeability, and chloride resistance of concrete. POFA was ground until the particles retained on sieve number 325 were less than 5% by weight. POFA was used to partially replace OPC at rates of 15, 25, and 35% by weight of binder. The water to binder (W/B) ratios of concrete were 0.40 and 0.50. The compressive strength, water permeability, and chloride resistance of concrete were investigated up to 90 days. The results showed that POFA concrete with W/B ratio of 0.40 had the compressive strengths ranging from 45.8 to 55.9 MPa or 82–94% of OPC concrete at 90 days, while POFA concrete with W/B ratio of 0.50 had the compressive strengths of 33.9–41.9 MPa or 81–94% of OPC concrete. Furthermore, the compressive strength of concrete incorporation of ground POFA at 15% was the same as OPC concrete. The water permeability coefficient and the chloride ion penetration of POFA concrete were lower than OPC concrete when both types of concrete had the same compressive strengths. The findings also indicated that water permeability and chloride ion penetration of POFA concrete were significantly reduced compared to OPC concrete.